Humoral regulation in remodeling of arterial vessels in patients with type 2 diabetes in combination with obesity: focus on omentin - Soloviuk, O. O.; Nazarenko, O. V.; Soloviul, O. A.; Солов'юк, Олександр Олегович; Назаренко, Олена Валеріївна (Kyiv : SPC “Sciconf.com.ua”, 2024)
Aim: to determine the level of omentin-1 in obese patients with type 2 diabetes and to assess the presence and nature of the relationship between its level and TIMS of the carotid arteries in these individuals.